What drives internationalization of new ventures? Evidence from India - Mohd Yasir Arafat; Ahmed Musa Khan; Mohd Shamim Ansari; Imran Saleem (Journal of Innovation and Entrepreneurship, 2022)
The researchers have already recognized the importance of entrepreneurship, but the role of new venture internationalization is still a matter of research. This study is measuring the influence of education, age, technology, fear of failure, and competition on new venture internationalization. It based on the interviews of 3413 respondents from India done by the Global Entrepreneurship Monitor. The influence of various factors on new venture internationalization has been measured through logistic regression. The technology, fear of failure, and competition have a significantly positive influence on new venture internationalization. This is one of the inceptive studies to measure the impact of education, age, technology, fear of failure and competition on new venture internationalization.
Keywords: 650; Age; Competition; Education; Fear of failure; Global Entrepreneurship Monitor; India; Logistic regression; New venture internationalization; Technology